Agile Governance Implementation in Public Services: the Case of DPMPTSP Padang City During the Covid-19 Pandemic - Ratih Ratih (JAKP (Jurnal Administrasi dan Kebijakan Publik))
The Covid-19 pandemic presents major challenges for Indonesia's health, economic and government sectors. In this context, the Padang City Investment and One-Stop Integrated Services Service (DPMPTSP) plays an important role in implementing local policies to support recovery. This research aims to explore the implementation of Agile Governance in DPMPTSP Padang City during the pandemic. The method used is descriptive qualitative, with data collection through in-depth interviews and document analysis. The research results show that the Padang City DPMPTSP has succeeded in implementing the principles of good enough governance, business-driven, human focused, and based on quick wins, so that it is able to improve public services and licensing innovation. Various innovations, such as the INDAH program for MSMEs and the OSS and SIMBG digital systems, are implemented to maintain service continuity. Apart from that, DPMPTSP also increases transparency and community participation through public consultation forums. The conclusion of this research confirms that the implementation of Agile Governance has enabled DPMPTSP to adapt and innovate in services, creating better relationships between government and society in the context of public services, especially in the midst of crisis conditions.